Outcome and toxicities of postmastectomy radiotherapy with integral cervicothoracic thermoplastic mask - Hongyan Zhang; Jieying Jin; Li Li; Linwei Wang; Qiuji Wu; Yahua Zhong (BMC Cancer, 2024)
Abstract Background Appropriate immobilization setup for postmastectomy radiotherapy may help to improve tumor control and to reduce radiation-related toxicities. This study aims at retrospectively evaluate the outcome and toxicities of postmastectomy radiotherapy (PMRT) with a novel integral cervicothoracic thermoplastic mask strategy. Methods Breast cancer patients were treated with modified radical mastectomy and PMRT. Patient immobilization setup was performed with the placement of a 1-cm thickened wax film on the ipsilateral chest wall and an integral cervicothoracic thermoplastic mask. PMRT was delivered according to the institutional protocol. Dose distribution, disease control, patient survival and radiation-induced toxicities were evaluated. Results Four-hundred nineteen eligible patients with complete follow-up information were included in the final analysis. The median follow-up was 40.2 (95%CI: 38.9–41.6) months. Two (0.5%) patients had local recurrence and 48 (11.4%) patients had distant metastasis. There were 22 (5.3%) deaths from all causes, of which 19 were caused by breast cancer. The 3-year overall survival (OS) rate was 94.8%. ER status, PR status, triple negative status, and T stages were significantly related to patient survival (p < 0.05). HER2 expression, N stage were not significantly related to patient survival. Most common radiation-induced toxicities included grade I (87.6%) and grade II (10.2%) dermatitis, and grade I pneumonitis (28.9%) found by chest X-ray or CT scans. No clinical detectable cardiovascular event related to radiotherapy was identified. Conclusion Postmastectomy radiotherapy with integral cervicothoracic thermoplastic mask leads to favorable outcome and moderate toxicities compared with results reported in literature and might be of clinical significance in breast cancer patient. However, this approach has not been compared directly with postmastectomy radiotherapy without immobilization, and its applicability in other regions with different treatment protocols requires further investigation.